THE CHANGES IN THE USAGE OF AGRICULTURAL LAND IN EASTERN REGION OF REPUBLIC OF MACEDONIA BETWEEN 1991 AND 2030 - Peshevski, Mile; Milovancević, Zoran (Economics of Agriculture, 2017)
This paper will present the analysis of the degree of changes in the usage of agricultural land in Eastern region of Republic of Macedonia. The basis for this analysis is statistical data for previous 23 years (1991 - 2013). The forecast presented here will encompass period of following 17 years, i. e by the year 2030. The method used in this process is trend extrapolation. Our calculations predict relatively large positive or negative changes in the future use of land. Different degree of changes can be seen among different arable crops. The usage of agricultural land shows negative changes in every category on regional level.